A utilização do software GeoGebra no ensino da geometria analítica - Brito, Marcos Alves de (2014)
In this thesis we aim, through the use of a technological tool, the computer, show the possibility of teaching Mathematics causing the student to build their knowledge from concepts presented with the help of software that allow viewing the activities developed. In this sense, we use the GeoGebra software, it is a dynamic geometry software in the public domain and its application to analytic geometry content is easy to learn for the user. Thus, we present a teaching sequence using GeoGebra software in teaching Analytic Geometry, following the contents of the Curriculum Proposal of the State of São Paulo. In each of the proposed activities develop the theoretical content with exercises followed by activity in GeoGebra. At the end of each activity are some of the comments made by students.